Answer:
x = 4
Explanation:
Okay so for this equation we have this:
-5(3x - 2)= - 50
because the 3x and -2 are in a parentheses that shows we have to multiply -5 we do like this:
(3x(-5) - 2(-5)) = -50
-15x + 10 = -50
Since we want to get rid of the 10 we are going to subtract 10 from both sides:
-15x + 10 = -50
- 10 -10
Since we are actually going to add -10 to -50 its going to look more like this:
-15x = -60
Now we are going to divide -15 from -15x and -60 in order to segregate -15 from x:
-15x/-15 = -60/-15
x = 4
Now we double check our work by placing 4 where x once was:
-5(3(4) - 2)= - 50
-5(12 - 2) = -50
-60 + 10 = -50
-50 = -50
Hope this helps